Analisis Partisipasi Masyarakat Dalam Perencanaan Pembangunan Desa di Kecamatan Gayam Kabupaten Bojonegoro - Mustofa, Moh.; Astuti, Hartiningsih; Putra, Bima Permana; Agung Sasmito, Dimas (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of education level, leadership style, and communication patterns on community participation in village development planning in Gayam District, Bojonegoro. This study uses a quantitative descriptive analysis method with data obtained through a structured questionnaire using a Likert scale, with a sample of 85 respondents selected using a purposive sampling technique. The analysis was carried out through data instrument testing, classical assumption tests, and multiple linear regression. The results showed that education level, leadership style, and communication patterns had a significant and positive effect on community participation. Communities with higher levels of education have a better awareness and understanding of the importance of the role of society in development. A good leadership style encourages active community involvement and an open and two-way communication pattern strengthens community trust in the village government. The implications of this study are the importance of the village government to improve the quality of community education, implement a good leadership style, and improve communication patterns to create good development planning.